Rates of Adverse Events in Hospitalized Patients After Summer-Time Resident Changeover in the United States: Is There a July Effect?. Issue 3 (12th April 2022) - Metersky, Mark L.; Eldridge, Noel; Wang, Yun; Eckenrode, Sheila; Galusha, Deron; Jaser, Lisa; Mathew, Jasie; Angus, Steven; Nardino, Robert
Abstract : Objectives: This study aimed to determine whether patients in teaching hospitals are at higher risk of suffering from an adverse event during the summer trainee changeover period. Methods: We performed a retrospective analysis of data from the Medicare Patient Safety Monitoring System, a medical-record abstraction-based database in the United States. Hospital admissions from 2010 to 2017 for acute myocardial infarction, heart failure, pneumonia, or a major surgical procedure were studied. Admissions were divided into nonsurgical (acute myocardial infarction, heart failure, or pneumonia) and surgical. Adverse event rates in July/August were compared with the rest of the year. Hospitals were stratified into major teaching, minor teaching, or nonteaching. Results were adjusted for patient demographics, comorbidities, and hospital characteristics. Outcomes were the adjusted odds of having at least 1 adverse event in July/August versus the rest of the year. Results: We included 185, 652 hospital admissions. The adjusted odds ratios (ORs) of suffering from at least one adverse event in a major teaching hospital in July/August was 0.83 (95% confidence interval [CI], 0.69–0.98) for nonsurgical patients and 1.09 (95% CI, 0.84–1.40) for surgical patients. In minor teaching hospitals, the adjusted ORs were 0.96 (95% CI, 0.88–1.04) for nonsurgical patients and 0.99 (95% CI, 0.87–1.12) for surgical patients. In nonteaching hospitals, the adjusted ORs were 0.98 (95% CI, 0.91–1.06) for nonsurgical patients and 1.10 (95% CI, 0.96–1.24) for surgical patients. Conclusions: Patients admitted to teaching hospitals in July/August are not at increased risk of adverse events. These findings should reassure patients and medical educators that patients are not excessively endangered by admission to the hospital during these months.